2020
DOI: 10.1016/j.jnucmat.2020.152005
|View full text |Cite
|
Sign up to set email alerts
|

Radiation damage tolerance of a novel metastable refractory high entropy alloy V2.5Cr1.2WMoCo0.04

Abstract: A novel multicomponent alloy, V2.5Cr1.2WMoCo0.04, produced from elements expected to favour a BCC crystal structure, and to be suitable for high temperature environments, was fabricated by arc melting and found to exhibit a multiphase dendritic microstructure with W-rich dendrites and V-Cr segregated to the inter-dendritic cores. The as-cast alloy displayed an apparent single-phase XRD pattern. Following heat treatment at 1187 °C for 500 hours the alloy transformed into three different distinct phases -BCC, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…Most refractory metals have high DBTTs in their pure form, and although efforts have been made to 'ductilise' some of them (for instance, adding Re to W [151]), the issue remains endemic and in most cases BCC refractory metals are found to be hard and brittle at room temperature. It is not surprising, therefore, that BCC refractory HEAs have typically been found to have high hardnesses in comparison to most conventional alloys, for example, References [16,[19][20][21]24,28,31,124], and the results of tensile tests are very rarely reported.…”
Section: Interstitials In Bcc Refractory Alloysmentioning
confidence: 99%
See 3 more Smart Citations
“…Most refractory metals have high DBTTs in their pure form, and although efforts have been made to 'ductilise' some of them (for instance, adding Re to W [151]), the issue remains endemic and in most cases BCC refractory metals are found to be hard and brittle at room temperature. It is not surprising, therefore, that BCC refractory HEAs have typically been found to have high hardnesses in comparison to most conventional alloys, for example, References [16,[19][20][21]24,28,31,124], and the results of tensile tests are very rarely reported.…”
Section: Interstitials In Bcc Refractory Alloysmentioning
confidence: 99%
“…A number of studies have found that some HEAs possess good phase stability under irradiation [ 49 , 51 , 52 , 54 , 55 , 67 , 93 , 94 , 95 , 110 , 122 , 123 , 124 ]. This behaviour has been attributed to a number of factors.…”
Section: The Potential Suitability Of Heas—irradiation Resistant?mentioning
confidence: 99%
See 2 more Smart Citations
“…The high mixing entropy of high-entropy alloys tends to form a solid solution; however, it is not easy to form an intermediate phase, which is important for the excellent properties of high-entropy alloys. High-entropy alloys have excellent thermal stability [18][19][20][21][22], radiation resistance [23][24][25][26], corrosion resistance [27][28][29][30][31][32][33][34][35], and mechanical properties [36][37][38][39][40][41][42]. High-entropy alloys are expected to be used in turbine blades and high-speed cutting tools, and lightweight high-entropy alloys [43] may be used in energy and transportation fields.…”
Section: Introductionmentioning
confidence: 99%